If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1.4x + 0.2 = -0.67x + -4 Reorder the terms: 0.2 + -1.4x = -0.67x + -4 Reorder the terms: 0.2 + -1.4x = -4 + -0.67x Solving 0.2 + -1.4x = -4 + -0.67x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.67x' to each side of the equation. 0.2 + -1.4x + 0.67x = -4 + -0.67x + 0.67x Combine like terms: -1.4x + 0.67x = -0.73x 0.2 + -0.73x = -4 + -0.67x + 0.67x Combine like terms: -0.67x + 0.67x = 0.00 0.2 + -0.73x = -4 + 0.00 0.2 + -0.73x = -4 Add '-0.2' to each side of the equation. 0.2 + -0.2 + -0.73x = -4 + -0.2 Combine like terms: 0.2 + -0.2 = 0.0 0.0 + -0.73x = -4 + -0.2 -0.73x = -4 + -0.2 Combine like terms: -4 + -0.2 = -4.2 -0.73x = -4.2 Divide each side by '-0.73'. x = 5.753424658 Simplifying x = 5.753424658
| 22x+78=22 | | 3(-7x+7)+8x=2(-7x+11)-5 | | 2(7-x)=30 | | (2*8)+4*5= | | -5v-1.5=1.5v+.2 | | 2(-x)=30 | | a^3+a^2-64a-64=0 | | d=2d-4 | | 12(5x-1)=7x(2x+2) | | 4(-6-4x)=-88 | | 3x^2+x^2-75x-25=0 | | 2n=-12 | | 12w+15w-4=-3w-4 | | 12x^2(x-1)=0 | | -[5x-(3x+1)]=-4-[3(2x-4)-2x] | | x+x-21=83 | | 9x^2-10y^2=0 | | 2.5w-4=-.5w-2.3 | | 5+1.7b=-2 | | 242r-18r^3=0 | | 17-y=200 | | 7=6q | | -[11x-(3x+10)]=-3-[4(3x-4)-2x] | | 6(-1x+3)=30 | | -1.5x+1.2=-6x-.5 | | Y=mx+c | | -4(6+x)=-44 | | 4[8-y]=2y+16 | | (4r-1)(5r+3)= | | 22-a+4a=7 | | 2y+y-3=4y-20 | | -16+49h^2=0 |